Competition Strategy of Online Retailers Considering Service Sensitivity and Cognitive Differences - ZHOU Xiaoxiang, HUANG Chengfeng, LI Hao (Jisuanji kexue yu tansuo, 2022)
In order to analyze the competitive behavior of online retailers in complex market under the environment of diversified customers, a duopoly competition model considering the service sensitivity and cognitive differences is established by using the Hotelling model. The equilibrium price, demand and revenue of static game and dynamic game are solved, and the changing trend is studied by numerical simulation. Results have shown that online retailers' profits are affected by the service sensitivity and cognitive differences, not only related to the price directly, but also relevant to unit service cost, brand cognition and competitors' pricing strategy highly. The high service providers with internet brand cognition have a significant price advantage, which means high service is always accompanied by high prices. Stray price effects exist in online retailers, blind to improve the quality of the cognitive service may do more harm than good for the low quality of service provider. Online retailers have the first-mover advantages. The previous decision maker's equilibrium profit is obviously higher than the latter, as well as the price. The dynamic equilibrium is also significantly better than the static equilibrium on profits and price. Online retailers have sufficient intrinsic motivation to grab the opportunity. There is a theoretical threshold for the service level of online retail, and merchants will not provide services beyond the threshold. Theoretical references can be provided on the pricing competition and service mode selection for online retailers in the context of big data.